Los límites de la tutela judicial efectiva al impugnar las decisiones de la autoridad de resolución bancaria Española - Lara Ortiz, María Lidón (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Effective judicial protection is considered a fundamental right which essence is access to jurisdiction. The literal diction of Article 24.1 of the Spanish Constitution gives an appearance of a broad civil access to protection of civil rights in judicial proceedings. However, it is not as broad as it may seem, as it only includes the right to obtain a judicial pronouncement in accordance with the provisions of the law that can be of inadmissibility of the challenge or of the initial claim, if the claim is not based on the legal presuppositions that allow the exercise action. Thus, there are areas in which the legal configuration of access to justice is so restrictive that it entails being locked out of jurisdiction in order to challenge many acts or settlements. This paper aims to analyse the limits of the challanges of the acts and pronouncements of the banking resolution authority in Spain, in order to verify whether – in spite of these limits – the constitutional guarantee of the effective judicial protection is undermined in these cases, or if such reduction in the scope of the banking regulation is admissible.